2018
DOI: 10.1292/jvms.18-0132
|View full text |Cite
|
Sign up to set email alerts
|

Detection of neutralizing antibody against porcine epidemic diarrhea virus in subclinically infected finishing pigs

Abstract: The purpose of this study was to detect porcine epidemic diarrhea virus (PEDV) subclinically infected pigs shipped from non-case farms to slaughterhouses. Systematic sampling was conducted at two slaughterhouses. A total of 1,556 blood samples were collected from 80 case and non-case farms from pigs over 6 months old. Blood samples were centrifuged to obtain sera. Serial serum dilutions were subjected to serological examination for PEDV presence using Neutralization test (NT). The cut-off titer was set at tite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 18 publications
(20 reference statements)
0
22
0
Order By: Relevance
“…When PEDV infection occurs on a pig farm, it usually spreads among pigs of different ages. However, pigs display age-dependent resistance to pathogenic PEDV infection (34,35). The virus accumulates and infects pregnant sows, and the subclinically infected sows transmit PEDV to the suckling piglets.…”
Section: Discussionmentioning
confidence: 99%
“…When PEDV infection occurs on a pig farm, it usually spreads among pigs of different ages. However, pigs display age-dependent resistance to pathogenic PEDV infection (34,35). The virus accumulates and infects pregnant sows, and the subclinically infected sows transmit PEDV to the suckling piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, PEDV infections occur sporadically in Japan (Ministry of Agriculture, Forestry and Fisheries of Japan). It has been reported that pig farms with no PEDV clinical signs contained subclinical PEDV seropositive animals, which were detected by NT [17]. Considering this situation for controlling PED, we need to survey and monitor the PEDV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Considering this situation for controlling PED, we need to survey and monitor the PEDV infection. NT is useful in sero-surveillance of both recent and post PEDV infection [17]. However, NT has some disadvantages such as being laborious, time consuming and mutated neutralizing related epitope.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of PEDV-positive farms in Vietnam was higher than that in the US and Japan (27.9% and 19.5%, respectively) (Alvarez et al 2016 ; Sasaki et al 2017 ) where syndromic surveillance has been carried out to help farm owners respond to PED outbreaks (United States Department of Agriculture and Service 2014 ; Ministry of Agriculture Forestry and Fisheries (MAFF) 2016 ). The results of a previous study provided evidence of the presence of seropositive animals on PEDV-negative farms (Koike et al 2018 ). In this study, PEDV was detected on 30.89% (101/327) of farms during the study period.…”
Section: Discussionmentioning
confidence: 83%
“…During current Vietnamese PED outbreaks, poor biosecurity procedures related to fomites, animals, and humans could be the major risk factors underlying nationwide PEDV transmission. Biosecurity practices such as using different trucks to carry pigs from different farms based on PEDV infection status, improving in farm hygiene management and avoiding risky practices associated with contact with pig excrement, were done to prevent the spreading of PEDV in Japan and US (United States Department of Agriculture and Service 2014 ; Koike et al 2018 ). Our results could contribute to producers to implement similar biosecurity measures to prevent the further spreading of PEDV in Vietnam.…”
Section: Discussionmentioning
confidence: 99%